Avoidant restrictive food intake disorder and suicidal ideation. (November 2022) - Robison, Morgan; Rogers, Megan L.; Robertson, Lee; Duffy, Mary E.; Manwaring, Jamie; Riddle, Megan; Rienecke, Renee D.; Grange, Daniel Le; Duffy, Alan; Plotkin, Millie; Blalock, Dan V.; Mehler, Philip S.; et al.
Highlights: This work is the first, to our knowledge, to recognize and address ARFID suicidal ideation presence and intensity within an adult population. This study compared adult ARFID suicidal ideation presence and intensity to that of other ED diagnoses. This work suggests that adult ARFID patients should be thoroughly and regularly screened for suicide risk. Abstract: Most DSM-5 eating disorder diagnoses are associated with elevated suicide risk; however, little is known about the relationship between Avoidant/Restrictive Food Intake Disorder (ARFID) and suicidal ideation. The aim of the current study was to examine suicidal ideation within an adult ARFID sample. Patients with eating disorders ( N = 936), some of whom met criteria for a current DSM-5 diagnosis of ARFID ( n = 79), completed the Beck Depression Inventory II Item 9, regarding suicidal ideation . The study was conducted within an eating disorder treatment facility that offers inpatient, residential, partial hospitalization program, and intensive outpatient levels of care. Findings suggest no significant pairwise differences in suicidal ideation prevalence between participants with ARFID and those with any other ED diagnosis. Thorough screening for suicidal thoughts and risk among those with ARFID is warranted at all levels of care. We suggest that future research expand upon this work in a larger adult ARFID sample.